The Role of the Binkamsa Unit in Preventing the Crime of Theft during the Covid-19 Pandemic in the Legal Area of the Batu Police - Reydenn Fidel Armada (Indonesian Journal of Police Studies, 2021)
The existence of the Covid-19 pandemic in Indonesia has caused problems in the health and economic fields which are marked by an increase in theft crimes in Batu City. The "PRESISI" National Police Chief Priority Program related to increasing the role of Pam Swakarsa as regulated in Perpol Number 4 of 2020 is expected to be able to increase the role of the Batu Police Binkamsa Unit. Therefore, a study was conducted that aims to describe and analyze the role of the Binkamsa Unit in preventing theft during the Covid-19 pandemic, identify the factors that influence the occurrence of theft, and find efforts to increase the role of the Binkamsa Unit in preventing theft. In this paper, the analytical tools are routine activity theory, management theory, and role theory. While the concepts used are the concept of Binkamsa and the concept of predictive policing. This study uses a qualitative approach and data collection through interviews, observations, and document studies. The research conducted is located in the jurisdiction of the Batu Police. Based on the research findings, the role of the Binkamsa Unit in preventing theft during the Covid-19 pandemic is still lacking at the management level, especially in planning, implementation and supervision. In addition, there are factors that influence the occurrence of theft in terms of perpetrators, victims, and the lack of adequate security. The efforts to increase the role of the Binkamsa Unit in preventing theft are analyzed using predictive policing theory. There are three choices of actions that can be taken, namely increasing resources, a specific crime approach, and a problem approach.